PRASASTI PENDEK DARI CANDI SANGGAR DAN KEMUNGKINAN PENGHORMATAN TERHADAP DEWA BRAHMA - Rita Istari (Balai Arkeologi Yogyakarta, 2015)
Sanggar temple is located on Penanjakan slope.. The hill is part of Wonogriyo of Pusungmalang village, Puspo regency, Pasuruan district. Sanggar temple suspected as place of worship to the God Brahma who dwells in Mount Bromo. On a series of research carried out in 2005-2008 by Yogyakarta Centre of Archaeology were found several short inscriptions around the temple to be praises used in religious rituals it is allegedly the people in the region. The tradition to sing praises by until the spread of Islam in Java. The adoption of Islam influence changes lasted praises. The contents of such literatur review espeally ancient writings are used to prove the assumptin.